Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines financial linkages and the correlation between Australian and U.S. output. It shows that the financial linkages have played an important role in conveying shocks from the United States to the Australian economy, and that these have become increasingly important in the 1990s. The paper examines income and output convergence across Australian states. It also examines the role of the terms of trade and different commodity prices in explaining the real exchange rate.